The City by the Bay : a magical journey around San Francisco - Brown, Tricia; Kleven, Elisa; Junior League of San Francisco (San Francisco : Chronicle Books, 1993)
A tour guide to the landmarks and interesting sights of San Francisco.
6.4
3-6
3-6
Elem. School Library Collection
Book Links (A.L.A.)
Booklist
Keywords: San Francisco (Calif.) -- Juvenile literature; San Francisco (Calif.) -- Guidebooks -- Juvenile literature; San Francisco (Calif.) -- Description and travel; San Francisco (Calif.) -- Description and travel